2017
DOI: 10.1177/0022219417704168
|View full text |Cite
|
Sign up to set email alerts
|

How Many U.S. High School Students Have a Foreign Language Reading “Disability”? Reading Without Meaning and the Simple View

Abstract: Conventional wisdom suggests that students classified as learning disabled will exhibit difficulties with foreign language (FL) learning, but evidence has not supported a relationship between FL learning problems and learning disabilities. The simple view of reading model posits that reading comprehension is the product of word decoding and language comprehension and that there are good readers and 3 types of poor readers-dyslexic, hyperlexic, and garden variety-who exhibit different profiles of strengths and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(76 reference statements)
2
16
1
Order By: Relevance
“…In these studies, U.S. high school students’ Spanish vocabulary and listening comprehension skills were found to be similar to the average native Spanish speaker at a 2½‐ to 3‐year‐old level, even after 3 years of Spanish courses (Sparks & Luebbers, ; Sparks et al, b). Other studies have shown that despite IDs in L1 achievement, U.S. high school students learned to decode an alphabetic L2 (Spanish) well but still met criteria for a L2 reading “disability” because they exhibited extraordinarily poor reading comprehension and listening comprehension skills, largely because of extremely limited L2 vocabulary acquisition (Sparks, ; Sparks & Luebbers, ; Sparks et al, ). The constraint on L2 learning, in particular vocabulary learning, for U.S. students in high school is the social context in which the learning takes place—that is, most live in a home and a community where the target language is not spoken.…”
Section: Pedagogical Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…In these studies, U.S. high school students’ Spanish vocabulary and listening comprehension skills were found to be similar to the average native Spanish speaker at a 2½‐ to 3‐year‐old level, even after 3 years of Spanish courses (Sparks & Luebbers, ; Sparks et al, b). Other studies have shown that despite IDs in L1 achievement, U.S. high school students learned to decode an alphabetic L2 (Spanish) well but still met criteria for a L2 reading “disability” because they exhibited extraordinarily poor reading comprehension and listening comprehension skills, largely because of extremely limited L2 vocabulary acquisition (Sparks, ; Sparks & Luebbers, ; Sparks et al, ). The constraint on L2 learning, in particular vocabulary learning, for U.S. students in high school is the social context in which the learning takes place—that is, most live in a home and a community where the target language is not spoken.…”
Section: Pedagogical Implicationsmentioning
confidence: 93%
“…Two instruments were used to assess L2 skills. Both instruments—the MLAT (Carroll & Sapon, ) to measure L2 aptitude and an informal measure of L2 (Spanish) phoneme awareness—were described in previous studies (see Sparks et al, ; Sparks & Luebbers, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized above, most formal studies of students’ learning outcomes in an FL have used mostly criterion‐referenced measures to compare speakers’ skills to specific criteria or domains of performance; however, studies have not compared monolingual native English–speaker learners’ skills with those of native speakers of the target language of the same age or grade level using a standardized measure. In three recent studies, Sparks and colleagues (Sparks, ; Sparks & Luebbers, ; Sparks & Patton, ) used a standardized measure of Spanish to assess the Spanish reading skills of monolingual English students in U.S. high schools and classified them according to reader types proposed by the simple view of reading model, a well‐researched model that explains how students acquire literacy skills (Gough & Tunmer, ; Hoover & Gough, ). The primary purposes of the present study were to (1) compare the achievement of monolingual English high school students in oral and written Spanish with that of native Spanish speakers on a standardized testing measure, and (2) propose appropriate expectations for monolingual English learners of Spanish after their completion of first‐, second‐, and third‐year high school Spanish courses.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…In several recent studies of L2 reading development, Sparks et al have proposed that the SVR model can also be used to explain the reading skills of monolingual U.S. high school students who are learning an L2 that also makes use of an alphabetic orthography (Sparks, ; Sparks & Luebbers, ; Sparks, Patton, & Luebbers, ). These studies have supported the SVR model by showing that L2 word decoding and L2 oral language (listening) comprehension make independent contributions to L2 reading comprehension.…”
mentioning
confidence: 99%